D6.6: 7 conference papers - Hadjimitsis, Diofantos G.; Nisantzi, Argyro; Themistocleous, Kyriacos; Mettas, Christodoulos; Evagorou, Evagoras G.; Agapiou, Athos; Lysandrou, Vasiliki; Christofe, Andreas; Tzouvaras, Marios; Papoutsa, Christiana; Loulli, Eleni; Neocleous, Kyriacos; et al. (My University, 2018)
The Deliverable 6.6 with the title “7 conference papers”, is part of WP6 “Dissemination and Exploitation” of Athena project with a basic aim to knowledge sharing, network development and exposure to an international environment. Three conference attendances were foreseen (e.g. CAA; SPIE; EARSeL) within the project duration whereas more than 30 posters and oral presentations were presented during the project in the conferences such as: SPIE 2016, SPIE 2018, EUROMED 2016, EUROMED 2018, EGU 2016, EGU 2017, EGU 2018, RSCy2016, RSCy 2017, RSCy 2018, etc.
Keywords: ATHENA project; Conference papers